Endless Chain of Cars Moving in a Tower of Glass
This is the famous "Nash Tower of Value" at the World's Fair in Chicago. A building of plate glass with a high glass tower in which Nash Sixes and Eights keep moving up and down, up and down, day and night. A dazzling spectacle.